INNOVATIVE CHANGES IN HUMAN RESOURCE MANAGEMENT IN TERMS OF ECONOMIC TURBULENCE IN UKRAINE - Rekun, Ganna; Pastukhova, Nina; Sardak, Yana (Social Economics, 1970)
The article discusses the importance of effective human resource management for sustainable development of the company in terms of economic turbulence in Ukraine. An important role, in this regard, plays innovation in human resource management, which influences an increase of flexibility, adaptability of modern Ukrainian companies during the crisis in the country and abroad. In this article we considered modern innovative methods of human resource management with effective practical application in domestic and foreign companies.